TINGKAT KEMAMPUAN BERPIKIR KRITIS SISWA SMA PADA MATERI FLUIDA DINAMIS - Dewi Novi Ginanjar Rahayu; Alex Harijanto; Albertus Djoko Lesmono (JURNAL PEMBELAJARAN FISIKA, 2018)
ABSTRACTOne of the goals of learning physics in schools is to improve students' criticalthinking skill. Critical thinking ability is the ability of the students in the process ofthinking in solving a problem in detail. By knowing the level of critical thinking it self,students can do introspection and have the desire and motivation to change for thebetter. In addition, students can also prepare for future exams such as nationalexamination as well as college entrance exam. As for the teacher, by knowing the levelof critical thinking skill of the students, the physics teachers can make it as a referenceto determine the learning strategy that will be used next. Therefore, it is necessary toidentify the level of critical thinking ability. The research method used is descriptiveresearch. The subjects of the study were students of grade XI IPA SMA. The datacollection method used is a test of description. The results of the study showed thatthe level of critical thinking ability of 18.63% of students were on a very highcategory, 42.16% of students were on a high category, 29.41% of students were in thecategory medium, 9.80% of students were on a low category, and no students were invery low category.Keywords: Physics, fluid dynamic, critical thinking